Valid serial length measurements in preterm infants permit characterization of growth patterns. (December 2018) - Pavageau, Lara; Rosenfeld, Charles; Heyne, Roy; Brown, L.; Whitham, Jenna; Lair, Cheryl; Brion, Luc
Abstract Background: The lack of a valid and safe method for measuring length in critically ill preterm neonates has led to a primary focus on weight gain. Local problem: Paucity of valid length measurements, precluding the accurate analysis of growth patterns. Methods: Quality improvement project among infants < 29 weeks or small for gestational age < 35 weeks with embedded validation of (1) a caliper (infantometer) for length measurements and (2) length measurements during the first week to estimate birth length. Intervention: Implementation of valid methods to measure length. Results: We validated infantometer measurements and first week length measurements. The percentage of neonates with valid measurements during the first week rose from 10% to 78%, resulting in increased identification of classifiable growth patterns from < 10% to 89%. Conclusions: By increasing the percentage of neonates with valid length measurements in the first week postnatal, we identified an increased number of neonates with classifiable growth abnormalities.